The talent pathways of professional and international female soccer players in the United States - Andrew, M.; Mannix, P.; Cost, R.; Oliva-Lozano, J. M. (Soccer & Society, 2026)
The overall structure of women`s soccer in the United States (US) renders a unique sport system within global soccer. This essay will examine the challenges and complexities of the talent pathway within youth female soccer in the US by exploring key components which have significant implications for long-term development including the country`s decentralized talent pathway, pay-to-play model, youth competition, talent identification programmes and collegiate soccer, and are analysed alongside sociocultural factors. Additionally, the professional women`s soccer ecosystem, including its significant growth and expansion, varying talent pathways will be examined, exemplifying and reinforcing the diverse, non-linear pathways to professional soccer in the US. Finally, the Women`s National Team`s success and future challenges are discussed. The recommendations provided emphasize the need for holistic understanding and adaptation to the ever-evolving women`s soccer landscape. This essay ultimately provides a foundation for future research and insights into fostering female-centred player development initiatives within the US.